Release of silicon and aluminum from montmorillonite surfaces in aqueous systems - Sondi, Ivan (Array, 2008)
Summary: The release of silicon and aluminum from purified Na-montmorillonite surfaces in aqueous systems was investigated in dependence of pH at 25 °C. This study has shown that the dissolution of montmorillonite solid involves several parallel and sequential physico-chemical processes. The initial fast exchange of surface cations by hydrogen ions is followed by the release of aluminum and silicon. The dissolution rate of Si is higher than that of Al and influenced by the relative ratios of basal siloxane and edge surfaces. It is quantitatively described by the dissolution rate constants depending on pH. These results are in agreement with the heterogeneity of montmorillonite surfaces and the dominant presence of the siloxane basal surface. The shift of pH to more basic values by the ion exchange processes, and the hydrolysis of dissolved species, induces the formation of secondary amorphous solids, which may serve as precursors for the formation of amorphous aluminosilicates